Efecto de la modulación del receptor para cannabinoide 1 (RCB1) sobre marcadores bioquímicos y conductuales de neurotoxicidad estriatal inducidos por el ácido 3 nitropropiónico (3-NP) en ratas - Maya López, Marisol (Universidad Autónoma Metropolitana, 2017)
CB1 receptors (also known as cannabinoid 1 receptors) are part of the endocannabinoid system (ESC) and participate in different physiological functions; they are abundant in the Central Nervous System and are mainly located in neuronal cells, where they regulate the synaptic functions at the presynaptic levels. Among these functions, CB1 inhibit the release of neurotransmitters such as glutamate (Glu) and gamma-aminobutiric acid (GABA). At the presynaptic level, they modulate the activity of GABAergic and glutamatergic receptors, inducing hypofunction of Nmethyl-D-aspartate receptors (NMDAr). CB1 receptors also participate in redox modulation. In this work, some processes linked with CB1 activity were evaluated in a rodent model of Huntington’s disease induced by the intrastriatal infusion of 3- nitropropionic acid (3-NP). 3-NP is a micotoxin derived from mushrooms and plants that blocks irreversibly the mitochondrial complex II (succinate dehydrogenase), thus inducing a decrease of ATP levels and an increase of free radical formation, favoring the process of secondary excitotoxicity due to neuronal depolarization and the subsequent NMDAr overactivation, which in turn allow a massive Ca2+ influx to further stimulate the death of striatal GABAergic neurons. First, we evaluated whether the CB1 receptor activation by the selective synthetic agonist of CB1, WIN 55,212-2, is able to protect the rat striatal tissue against the damage induced by 3-NP. For this purpose, WIN 55,212-2 (1 mg/kg i.p. x 6 days) was administered as a pretreatment to rats, and behavioral and biochemical parameters related with 3-NP-induced (500 nmol/µl, intrastriatal bilateral infusion) toxicity were evaluated in adult male Wistar rats x (280-320 g). Locomotor activity was estimated by the open field test, whereas the extent of tissue damage was evaluated by the hematoxilin & eosin (H&E) staining.; Los receptores para cannabinoides 1 (RCB1) son parte del sistema endocannabinoide (SEC) y participan en diversas funciones del sistema nervioso central (SNC). En neuronas, los RCB1 inhiben la liberación del ácido ?-aminobutírico (GABA) y glutamato a nivel presináptico, mientras que a nivel postsináptico modulan la actividad de otros receptores que pueden ser GABAérgicos y glutamatérgicos, induciendo la hipofunción de receptores para N-metíl-D-aspartato (NMDA). También se ha demostrado que participan en la modulación redox. El WIN 55,212-2 es un cannabinoide sintético con mayor afinidad a los RCB1 que se utiliza en la investigación para explorar los mecanismos del SEC. El ácido 3-nitropropiónico (3- NP) es una micotoxina derivada de hongos y plantas que bloquea irreversiblemente al complejo II mitocondrial, también conocido como succinato deshidrogenasa (SDH). El 3-NP inhibe la producción de ATP, aumenta la producción de radicales libres y favorece la excitotoxicidad indirecta por desregulación del voltaje neuronal, con la consecuencia activación de receptores tipo NMDA y el alto flujo de calcio que lleva a la muerte celular de neuronas GABAérgicas del estriado.